Resolving small-scale cold circumgalactic gas in TNG50. Issue 2 (2nd September 2020) - Nelson, Dylan; Sharma, Prateek; Pillepich, Annalisa; Springel, Volker; Pakmor, Rüdiger; Weinberger, Rainer; Vogelsberger, Mark; Marinacci, Federico; Hernquist, Lars
ABSTRACT: We use the high-resolution TNG50 cosmological magnetohydrodynamical simulation to explore the properties and origin of cold circumgalactic medium (CGM) gas around massive galaxies ( M ⋆ > 10 11 M⊙ ) at intermediate redshift (z 0.5 ). We discover a significant abundance of small-scale, cold gas structure in the CGM of 'red and dead' elliptical systems, as traced by neutral H i and Mg ii . Halos can host tens of thousands of discrete absorbing cloudlets, with sizes of order a kpc or smaller. With a Lagrangian tracer analysis, we show that cold clouds form due to strong δ ρ / ρ 1 gas density perturbations that stimulate thermal instability. These local overdensities trigger rapid cooling from the hot virialized background medium at ∼10 7 K to radiatively inefficient ∼10 4 K clouds, which act as cosmologically long-lived, 'stimulated cooling' seeds in a regime where the global halo does not satisfy the classic t cool / t ff < 10 criterion. Furthermore, these small clouds are dominated by magnetic rather than thermal pressure, with plasma β ≪ 1, suggesting that magnetic fields may play an important role. The number and total mass of cold clouds both increase with resolution, and the m gas ≃ 8 × 10 4 M⊙ cell mass of TNG50 enables the ∼ few hundred pc, small-scale CGM structure we observe to form. Finally, we make a preliminary comparison against observations from the COS-LRG, LRG-RDR, COS-Halos, and SDSS LRG surveys. We broadly find that our recent, high-resolution cosmological simulations produce sufficiently high covering fractions of extended, cold gas as observed to surround massive galaxies.